Foreign Equity Investment Restrictions, Capital Flight, and Shareholder Wealth Maximization: Theory and Evidence - Stulz, René M.; Wasserfallen, Walter (Review of Financial Studies, 1995)
This article provides a theory of foreign equity investment restrictions. We consider a model where the demand function for domestic shares differs between domestic and foreign investors because of deadweight costs in holding domestic and foreign securities that depend on the country of residence of investors. We show that domestic entrepreneurs maximize firm value by discriminating between domestic and foreign investors. The model implies that countries benefitting from capital flight have binding ownership restrictions such that foreign investors pay a higher price for shares than domestic investors. The empirical implications of this theory are supported by evidence from Switzerland. Article published by Oxford University Press on behalf of the Society for Financial Studies in its journal, The Review of Financial Studies.